2017
DOI: 10.1080/13218719.2017.1347935
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Violent and Non-violent Versatility in Self-reported Juvenile Delinquency

Abstract: Situational action theory (SAT) has emphasized the interaction between individual and social influences on youth crime involvement. In this study, attitudes towards violence, self-control and perception of neighbourhood are tested in order to determine to what extent they predict versatility in violent and non-violent offences. In order to attain this goal, 2309 Belgian youths aged from 12 to 18 years were administered the Self-report Delinquency Questionnaire. When the offences are divided into violent and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
1
6
0
2
Order By: Relevance
“…Rule-breaking constituted the most common form of antisocial behaviour, in line with some previous research (e.g., Becht, Prinzie, Deković, van den Akker & Shiner, 2016). It is worth noting that some studies reported physical aggression as the most common form of antisocial behaviour in adolescents (Cuervo, Villanueva, Born & Gavray, 2018;Modecki, Uink & Barber, 2018). The obtained results are in relatively good agreement with the findings of earlier domestic studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Rule-breaking constituted the most common form of antisocial behaviour, in line with some previous research (e.g., Becht, Prinzie, Deković, van den Akker & Shiner, 2016). It is worth noting that some studies reported physical aggression as the most common form of antisocial behaviour in adolescents (Cuervo, Villanueva, Born & Gavray, 2018;Modecki, Uink & Barber, 2018). The obtained results are in relatively good agreement with the findings of earlier domestic studies.…”
Section: Discussionsupporting
confidence: 86%
“…Кршење норми представљало је најчешћи облик антисоцијалног понашања, што је у складу са резултатима неких претходних истраживања (нпр Becht, Prinzie, Deković, van den Akker & Shiner, 2016),. мада постоје студије у којима је физичка агресија најчешћи облик антисоцијалног понашања адолесцената(Cuervo, Villanueva, Born & Gavray, 2018;Modecki, Uink & Barber, 2018).…”
unclassified
“…Violent recidivism was defined as any new criminal conviction for a violent offense (e.g., assault, robbery, murder, sexual offenses). Although no classification of violent/nonviolent crime is proposed by the legal system in Spain, the charges were classified based on previous studies (Cuervo et al, 2018; Junger-Tas et al, 2010). The data for the adult criminal proceedings were collected at the Offices of the Coordinator of Administrative Justice in a Spanish province, between the youth’s age of majority (18 years old in Spain) and November 2016, when the data were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Although the military and INGOs largely frame violent and non-violent social order respectively, there are areas of overlap and interdependence (Cuervo et al 2018). The military is not restricted to framing violent social order.…”
Section: Contextualising P/cve and Modelling The Violent And Non-viol...mentioning
confidence: 99%